Eklektisisme pada Fasad Bangunan sebagai Ekspresi Identitas Kelokalan : (Kasus: Kantor Bupati Rote Ndao) - Fanggidae, Dodi; Bahar, Yudi (RUAS, 2023)
Problems that arise in a time when it is easy to obtain information and references result in the emergence of a tendency to use various architectural styles, resulting in problems where the use of these styles is different from the local context in the area. Eclecticism in architectural design can be one method to produce local identity in new buildings. This can be achieved if the references used in the design come from the right sources. The method of analysis of the composition of the façade is used to understand the visual expression of the façade. This research reveals the expression of Rote Ndao's local identity through eclecticism on the architectural façade of the Regent's Office. The results showed that the Regent Office presented local identity through four eclecticism approaches. Ti'i langga and bohani elements are ornaments on the roof (art and decoration), so it is interpreted as a symbol of the highest government in this region (symbol). The combination of Rote Ndao, Ti'i Langga traditional roofs, and designs with modern materials becomes a pluralism concept on the façade of the building, namely historical references and present-day architecture. This study is relevant to understanding and safeguarding cultural heritage. The integration of local elements in architectural design allows development that fulfills functions and respects cultural heritage.